EPSA Philosophy of Science: Amsterdam 2009 2011
DOI: 10.1007/978-94-007-2404-4_13
|View full text |Cite
|
Sign up to set email alerts
|

The Uninvited Guest: ‘Local Realism’ and the Bell Theorem

Abstract: According to a wrong interpretation of the Bell theorem, it has been repeatedly claimed in recent times that we are forced by experiments to drop any possible form of realism in the foundations of quantum mechanics. In this paper I defend the simple thesis according to which the above claim cannot be consistently supported: the Bell theorem does not concern realism, and realism per se cannot be refuted in itself by any quantum experiment. As a consequence, realism in quantum mechanics is not something that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…The first remark to be made, before analyzing how RQM is supposed to implement the above attitude, is that RQM grounds its reading of EPR correlations on an alternative between 'strong realism' and locality which in fact is mistakenly assumed to be the core of Bell's theorem. In the RQM approach, the relativization of states and the ensuing lack of observer-independence are taken to realize a suitable weakening of an alleged 'strong realism' but, in fact, such realism does not belong to the set of independent assumptions of Bell's theorem (Laudisa 2012(Laudisa , 2017. As is well known, the EPR argument can be formulated as an inference from three conditions to the 8 Eminent physicists have shared this attitude, such as Nobel laureate Sir Antony J. Leggett: "I believe that the results of the present investigation provide quantitative backing for a point of view which I believe is by now certainly well accepted at the qualitative level, namely that the incompatibility of the predictions of objective local theories with those of quantum mechanics has relatively little to do with locality and much to do with objectivity."…”
Section: Rqm and The Epr-bell Non-locality Issuementioning
confidence: 99%
“…The first remark to be made, before analyzing how RQM is supposed to implement the above attitude, is that RQM grounds its reading of EPR correlations on an alternative between 'strong realism' and locality which in fact is mistakenly assumed to be the core of Bell's theorem. In the RQM approach, the relativization of states and the ensuing lack of observer-independence are taken to realize a suitable weakening of an alleged 'strong realism' but, in fact, such realism does not belong to the set of independent assumptions of Bell's theorem (Laudisa 2012(Laudisa , 2017. As is well known, the EPR argument can be formulated as an inference from three conditions to the 8 Eminent physicists have shared this attitude, such as Nobel laureate Sir Antony J. Leggett: "I believe that the results of the present investigation provide quantitative backing for a point of view which I believe is by now certainly well accepted at the qualitative level, namely that the incompatibility of the predictions of objective local theories with those of quantum mechanics has relatively little to do with locality and much to do with objectivity."…”
Section: Rqm and The Epr-bell Non-locality Issuementioning
confidence: 99%
“…The meaning of the locality assumption is mostly uncontroversial. But physicists and philosophers sustaining that the Bell theorem is a quantum nonlocality theorem strongly resist the realism hypothesis [3,4,[6][7][8]. Here we analyze the usually assigned meanings of the term realism and whether Bell-type experiments can falsify it.…”
Section: Locality and Realismmentioning
confidence: 95%
“…A poll carried out in 2011 [1] reported that 64% of the surveyed scientists interpret the observed violations of Bell's inequalities as the untenability of local realism. But some proponents of quantum nonlocality strongly resist the expression of local realism [2][3][4][5], while those who accept its use do not always agree on its precise meaning.…”
Section: Introductionmentioning
confidence: 99%
“…It is simply a statement of something we know is true -a mathematical proof of it. [25] The controversy around the classical or non-classical nature of the Bell inequality and the esoteric tied-up issue of realism is a red herring that only diverts from the actual nonlocality argument [6,7,9,[11][12][13][26][27][28], namely the EPR reasoning.…”
Section: The 1964 Bell Theoremmentioning
confidence: 99%
“…The various and sometimes obscure ponderings about realism notwithstanding [26][27][28]38], there is a clear meaning for which its rejection would allow saving locality. Van Fraassen [18] expressed this view as ...empirical adequacy of a theory consists in it having a model that all the (models of) actual phenomena will fit into.…”
Section: Rejecting Realismmentioning
confidence: 99%